Estudos Hematológicos De Caprinos Infectados Experimentalmente Com Gaigeria pachyscelis Bailliet & Henry 1910 (Nematoda: Ancylostomatoidea) - Nascimento, Adjair Antonio do; Arantes, Isaú Gouveia; Artigas, Paulo de Toledo; Santana, Áureo Evangelista (Semina: Ciências Agrárias, 1990)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Fifteen crossbred goats 4 months old, reared in worm-free conditions were experimentally infected with progressive amounts of Gaigeria pachyscelis larvae (150, 300, 600, 1200 and 2400 larvas). Some blood parameters as red cells count, haemoglobin and packed-cell volume decreased significanthy as consequence either of the length of time or the amount of larvae found in the gut. The reduction in haemoglobin levels appeared earlier than the other parameters under study. It was also noted light differences in leukocytes total count and eosinophilia. Most of the animals developed at the end of experimental period normocytic and normochromic anaemia.